2004
DOI: 10.1002/lt.20049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of early hepatocellular carcinoma

Abstract: Early hepatocellular carcinoma (HCC) is defined as a well-differentiated cancer containing Glisson's triad, but it remains unknown whether this lesion is curable by surgery. We studied 70 patients who had a single HCC smaller than 2 cm in diameter (Stage T1) and who underwent curative hepatectomy and long-term follow-up. Based on our typing system, the tumors were assigned as early HCC (n=15), overt HCC (n=52), and non-HCC tumor (n=3). The rate of microscopic regional spread was lower in early HCCs than in ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…In our institution, Gd-EOB-DTPA is currently the first choice of contrast agent in liver MR studies for evaluating these lesions, because the HB-phase assists in better diagnosing early HCCs, which have a high chance of being cured and a low risk of recurrence [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, Gd-EOB-DTPA is currently the first choice of contrast agent in liver MR studies for evaluating these lesions, because the HB-phase assists in better diagnosing early HCCs, which have a high chance of being cured and a low risk of recurrence [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…However, intrahepatic recurrence due to secondary primary HCC is often seen even in patients with early HCC [27, 28]. Takayama et al [25] reported that the 5-year recurrence-free rate was 53 % in patients with early HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, postresection tumor recurrence is common, with a 5-year recurrence rate >50% [1, 2, 11, 12]. In all, 80% of the recurrences develop within the liver remnant [13], so it is important for surgeons to select the most appropriate treatment for patients with recurrent HCC.…”
Section: Discussionmentioning
confidence: 99%